Incomplete Information and Multiple Machine Queueing Problems - Manipushpak Mitra (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
In mechanism design problems under incomplete information, it is generally difficult to find decision problems that are first best implementable. A decision problem under incomplete information is first best implementable if there exists a mechanism that extracts the private information and achieves efficiency with a transfer scheme that adds up to zero in every state. One such problem is the queueing problem with one machine. In this paper we identify the conditions on cost structure for which queueing problems with multiple machines are first best implementable.
Keywords: C44; C72; C78; D82; 330; Queueing Problems; First Best Implementability